Baseball : The Turbulent Midcentury Years - Gietschier, Steven Philip, 1948- (Book collections on Project MUSE., 2023)
"A history of baseball as a sport and business during the middle of the twentieth century, examining the game on and off the field and tracing its development within the broader contours of American history"--